Deep Learning-Driven Mobility And Utility-Based Resource Management In Mm-Wave Enable Ultradense Heterogeneous Networks - Ukasyah bin Mahamod (Universiti Sains Islam Malaysia, 2025)
Matric: 4201119 (FKAB)